Anonim şirketlerin haklı sebeple feshi davasındaki fesih dışı çözüm yolları - Atila, Beste (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
The solutions except of annulment in the suit for annulment of the joint-stock corporation by just cause